Regulation of L-Lactate in Glutamate Excitotoxicity Under Cerebral Ischemia: Pathophysiology and Preventive Strategy - Mao Zhang; Yanyan Wang; Zili Gong; Wen Jiang; Guodong Ge; Hong Guo (Pharmaceuticals, 2025)
Glutamate is an excitatory neurotransmitter in the central nervous system (CNS) that mediates synaptic transmission. However, glutamate homeostasis among neural cells is broken in cerebral ischemia. Excessive glutamate triggers N-methyl-d-aspartate receptors (NMDARs) in postsynaptic neurons, leading to intracellular calcium (Ca2+) overload and excitoneurotoxicity. At this moment, L-lactate may affect NMDARs and play a protective role in cerebral ischemia. This work proposes that L-lactate regulates glutamate signaling among neural cells. But, dysregulation of L-lactate in glutamate signaling cascades contributes to glutamate excitotoxicity in cerebral ischemia. In detail, L-lactate regulates the glutamine(Gln)-glutamate cycle between astrocytes and presynaptic neurons, which triggers the astroglial L-lactate-sensitive receptor (LLR)-cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) pathway, coordinating astroglial glutamate uptake and neuronal glutamate transmission. L-lactate mediates glutamate signaling and synaptic transmission among neural cells. In addition, L-lactate promotes the function of mitochondrial calcium uniporter complex (MCUC), which quickly depletes intracellular Ca2+ in postsynaptic neurons. In addition, L-lactate can promote the conversion of microglia from the pro-inflammatory (M1) to anti-inflammatory (M2) phenotype. Therefore, regulation of L-lactate in glutamate signaling in the CNS might become a preventive target for cerebral ischemia.